The Role of the Community in Strengthening the Functionsof Witness and Victim Protection Agencies in Indonesia - Situmeang, Sahat Maruli Tua; Pane, Musa Darwin; Mile, Tiara; Rachim, Rizal Aulia (LEGAL BRIEF, 2024)
Active community engagement and participation in witness and victim protection programs in Indonesia remain low due to a lack of understanding of program benefits and difficulties accessing information. This study aims to identify the primary barriers and develop strategies to enhance community participation in the witness and victim protection programs managed by the Witness and Victim Protection Agency (LPSK). A descriptive-qualitative research method was employed, utilizing primary data collected through in-depth interviews and focus group discussions, along with secondary data from official documents and literature reviews. The findings indicate that reforming communication strategies, utilizing digital platforms, and strengthening partnerships with civil society organizations and higher education institutions can address these barriers. The implications of this research highlight the need for adapting informational materials to local contexts and improving information accessibility to bolster community participation. These recommendations aim to enhance program effectiveness and ensure the benefits are maximized for the community